Meet Dave - Berg, John; Komarnicki, Todd; Friendly, David T., John; greenberg, Rob, John; Corbett, Bill; Robbins, Brian; Twentieth Century Fox; Regency Enterprises ([California] : 20th Century Fox Home Entertainment, 2008)
Dave Ming Chang (Eddy Murphy) is an alien spaceship, on a mission to Earth to save his home planet. Torn between the voices in his head, a tiny alien crew ledby a high-strung, miniature version of himself, and the world around him, Dave struggles to appear normal. But when he falls for an Earth woman, the consequences are hillarious in this cleverly conceived...comedy with plenty of loughs
Title from title screen
Special features: gag reel, deleted scenes, alternate endings, the making of meet dave, crew confessions, making a scene
Executive producers, Arnon Milchan, Thomas M. Hammel ; director of photography, Clark Mathis, film editoe, Ned Bastille
Cast: Eddy Murphy, Elizabeth Banks, Gabrielle Union, Scott Caan, Ed Helms, Kevin Hart
DVD Format
Dolby digital
Keywords: Human-alien encounters -- Drama; Space ships -- Drama; Extraterrestrial beings -- Drama